Construction of Sports Nutrition Dynamic Intervention Mechanism Based on the Improvement of College Students' Physical Health. (2nd August 2022) - Wang, Dongsheng; Chen, Baoping
Abstract : Exercise can improve people's physical health and strengthen their body bones. But the physique of college students is generally too poor. The enhancement of College Students' physique cannot be completed in a day. This study aims to explore the best sports nutrition intervention scheme for strengthening college students' physique from the construction of sports nutrition dynamic intervention mechanism, so as to provide theoretical reference for public physical education teaching and students' independent exercise. In this study, 100 full-time associate students in our university were selected as the research objects. Before the experiment, the subjects' body shape, body function, and physical quality were tested. Based on the random mathematical method, the full-time associate students were randomly divided into four groups: control group, exercise intervention group, nutrition intervention group, and sports nutrition intervention group, with 25 people in each group. After the experiment, the body shape, body function, and physical quality of the four groups were tested. The results show that exercise and nutrition intervention have little effect on college students' height, but have great influence on body mass index, vital capacity and 800 meter running. Especially after the experiment, the vital capacity of the exercise group and the sports nutrition group increased by nearly 250 ml and 500 ml, respectively, and the 800 m running time increased by nearly 10 s and 18 s, respectively. Strengthening exercise and increasing nutritional intake can effectively improve the institutional health of college students.